Tegeltableau. Met tekst: 'Arbeid heeft geen waarde tenzij men erin gelooft'. Aangeboden door de leden 1919-1959
Tegeltableau. Met tekst: 'Arbeid heeft geen waarde tenzij men erin gelooft'. Aangeboden door de leden 1919-1959.